2002
DOI: 10.1142/s1609945102000151
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Assessing the Feasibility of Construction Project in Contributing to the Attainment of Sustainable Development

Abstract: Construction activity is commonly considered to have adverse impacts on the environment, which is the basis of sustainable development for human being. It is considered that the proper development and operation of a construction project can make significant contribution to the mission of sustainable development. However, the existing difficulty is the lack of the guidance for implementing sustainable development principles in construction business. Whilst the concept of sustainable construction has become popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Special emphasis has been placed on the attempts for reducing waste generation and improving techniques in minimization of the harmful effects of construction activities on the environment. Many research efforts have been done on environmental concerns in the construction industry, including impacts of rapid infrastructure growth on the environment (Shen & Zhang, 2002;Zhang, Shen, & Scott, 2000); examination on the waste flows and control on construction sites (Shen, Tam, Tam, & Drew, 2004;Tam, Shen, Fung, & Wang, 2007); approaches for assessing the feasibility of a construction projects in contributing to the attainment of sustainable development (Shen, Wu, & Wang, 2002); assessment of sustainable performance of construction projects and contractor activities (Shen, Lu, Yao, & Wu, 2005;Shen & Tam, 2002;Shen, Wu, Chan, & Hao, 2005;Shen & Yao, 2006;Tam, Tam, Shen, Zeng, & Ho, 2006).…”
Section: Sustainable Construction Practicesmentioning
confidence: 99%
“…Special emphasis has been placed on the attempts for reducing waste generation and improving techniques in minimization of the harmful effects of construction activities on the environment. Many research efforts have been done on environmental concerns in the construction industry, including impacts of rapid infrastructure growth on the environment (Shen & Zhang, 2002;Zhang, Shen, & Scott, 2000); examination on the waste flows and control on construction sites (Shen, Tam, Tam, & Drew, 2004;Tam, Shen, Fung, & Wang, 2007); approaches for assessing the feasibility of a construction projects in contributing to the attainment of sustainable development (Shen, Wu, & Wang, 2002); assessment of sustainable performance of construction projects and contractor activities (Shen, Lu, Yao, & Wu, 2005;Shen & Tam, 2002;Shen, Wu, Chan, & Hao, 2005;Shen & Yao, 2006;Tam, Tam, Shen, Zeng, & Ho, 2006).…”
Section: Sustainable Construction Practicesmentioning
confidence: 99%
“…Environmental category refers to conserving and managing resources as well as contributing to the environmental protection of the project location, whereas the social factors mean respecting human rights and equal opportunities and improving the community development (Bjärstig, 2017). The three groups of categorizing sustainability factors have also been employed in other related research studies (Shen, Wu, & Wang, 2002;Ugwu, Kumaraswamy, Wong, & Ng, 2006); for example, Martens and Carvalho (2017) developed a cross-model analysis by adopting the three-P concept. Similarly, Yu et al (2018) reviewed 26 related papers and identified 38 sustainability factors for PPP projects, which were categorized according to the three-P concept.…”
Section: Concept Of Sustainabilitymentioning
confidence: 99%
“…In fact, only through making great efforts to enhance microscopic areas of research and practice can the macro and meso level sustainable development be implemented. Among various kinds of projects, construction projects are commonly considered to have adverse impacts on the natural environment which is the basis of sustainable development for human beings (Tse 2001;Shen et al 2002). Hence the concept of sustainability should be at the center of all construction projects, whatever their scale.…”
Section: Introductionmentioning
confidence: 99%
“…There is little existing work providing methods to assess the degree of the contribution of developing a construction project to the attainment of sustainable development (Shen et al 2002). It would be understandable if it was just a matter of technology, but the lack of attention paid to the urgency and importance of such research is not excusable, it makes the lack of the guidance for implementing sustainable development in construction industry.…”
Section: Introductionmentioning
confidence: 99%